Environmental legislation of ukraine: towards the european union standards - Yakymenko, Igor; Dotsenko, Olena; Negretova, Victoria; Pobuta, Oleksandra; Hrychenko, Maryna; Madzhd, Svitlana (My University, 2024)
Environmental legislation of Ukraine is based on the fundamental principles of sustainable development and constitutes an important part of the national legislation. It includes a number of articles of the Constitution of Ukraine, the Law of Ukraine on Environmental Protection, relevant articles of the Code of Ukraine on Administrative Offenses and the Criminal Code of Ukraine among many others. Starting from 2014, Ukraine began implementing the key elements of the EU legislation in terms of the EU – Ukraine Association Agreement. According to the Cabinet of Ministry of Ukraine, currently Ukraine has implemented about 80% of the European Union legal norms on environmental protection into the national legislation. A good example of the effective implementation of the EU laws into the legislation of Ukraine is the new Law of Ukraine on Waste Management (2022), which introduced basic European principles and hierarchy of waste management into Ukrainian legislative landscape. Meanwhile, one of the crucial parts of the legislation of Ukraine, which still needs a radical upgrade, is a set of norms for legal responsibility for environmental offences. Due to the outdated Code of Ukraine on Administrative Offenses, the state can currently impose only a symbolic fine for environmental offences. These norms rather provoke potential wrongdoers to break the laws than to follow good social practices. However, all parts of the society, including citizens, business circles, authorities and social services are deeply interested in maintaining clean environment now and for the future generations. Consequently, the legislative changes should be implemented urgently, even despite the other huge challenges for the country during these days

Екологічне законодавство України базується на фундаментальних принципах сталого розвитку та є важливою частиною національного законодавства. Воно включає низку статей Конституції України, Закону України про охорону навколишнього середовища, відповідні статті Кодексу України про адміністративні правопорушення та Кримінального кодексу України, серед багатьох інших. Починаючи з 2014 року, Україна почала імплементувати ключові елементи законодавства ЄС у рамках Угоди про асоціацію між ЄС та Україною. За даними Кабінету Міністрів України, наразі Україна імплементувала близько 80% правових норм Європейського Союзу щодо охорони навколишнього середовища у національне законодавство. Гарним прикладом ефективної імплементації законодавства ЄС у законодавство України є новий Закон України «Про управління відходами» (2022), який запровадив основні європейські принципи та ієрархію управління відходами в українське законодавство. Тим часом, однією з ключових частин законодавства України, яка все ще потребує радикального оновлення, є звід норм щодо юридичної відповідальності за екологічні правопорушення. Через застарілий Кодекс України про адміністративні правопорушення держава наразі може накладати лише символічний штраф за екологічні правопорушення. Ці норми радше провокують потенційних правопорушників на порушення законів, ніж на дотримання належних соціальних практик. Однак усі верстви суспільства, включаючи громадян, бізнес-коле, владу та соціальні служби, глибоко зацікавлені у збереженні чистого довкілля зараз і для майбутніх поколінь. Отже, законодавчі зміни мають бути впроваджені терміново, навіть попри інші величезні виклики, з якими стикається країна в ці дні
Keywords: environmental protection; European legislation; Ukrainian legislation; environmental offences; legal responsibility; кафедра екології та екоменеджменту; захист навколишнього середовища; Європейське законодавство; Українське законодавство; екологічні правопорушення; юридична відповідальність